Disparities in Technical and Vocational Education Attrition in the Philippines: From Enrollment to Certification - Abao, Jackielyn; Balaba, Christopher; Cap-atan, Mark Alain; Cosmiano, Charlie; Mahinay, Ray Butch (Journal of Interdisciplinary Perspectives, 2025)
This study explores national and regional disparities in attrition across the Technical and Vocational Education and Training (TVET) pipeline in the Philippines, focusing on the transition from enrollment to TESDA certification. Despite rising national enrollment and graduation figures, significant leakages persist between critical stages—graduation, assessment, and certification. Using a descriptive-comparative research design and 2024 secondary data from TESDA, this study analyzes performance across all 17 regions, calculating attrition percentages and visualizing disparities through statistical tables and graphs. Findings reveal an overall national attrition rate of 14%, with the most substantial drop (5.93%) occurring between assessment and certification. Some regions, including CARAGA, CAR, and Region IX, exhibit alarmingly high total attrition rates exceeding 50%, underscoring the systemic barriers that hinder learners from completing the certification process. In contrast, regions such as VI and VIII show more favorable outcomes, highlighting the uneven distribution of TVET support and access across the country. Contributing factors to high attrition include limited access to assessment centers, weak industry linkages, and infrastructure deficits, particularly in geographically isolated and disadvantaged areas. The study underscores the need for region-specific, stage-targeted interventions to improve retention and certification outcomes. Strengthening public-private partnerships, enhancing assessment accessibility, and aligning programs with local labor market needs are recommended to bridge the gaps. These findings offer policy-relevant insights for TESDA and stakeholders in designing a more inclusive, responsive, and equitable TVET system that advances national goals in skills development and human capital formation